2021
DOI: 10.1002/chem.202004988
|View full text |Cite
|
Sign up to set email alerts
|

π‐Bridge Substitution in DASAs: The Subtle Equilibrium between Photochemical Improvements and Thermal Control**

Abstract: Donor–acceptor Stenhouse adducts (DASAs) are playing an outstanding role as innovative and versatile photoswitches. Until now, all the efforts have been spent on modifying the donor and acceptor moieties to modulate the absorption energy and improve the cyclization and reversion kinetics. However, there is a strong dependence on specific structural modifications and a lack of predictive behavior, mostly owing to the complex photoswitching mechanism. Here, by means of a combined experimental and theoretical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…These chemotypes have attracted enormous attention owing to their facile preparation as well as their unique negative photochromic properties. [11,32,[156][157][158][159][160] DASAs are colored in the extended state and undergo Z-E isomerization and subsequent thermal conrotatory 4π electrocyclization to the compact state upon irradiation with visible light (Figure 17a,b). [161][162][163][164] Until now, three generations of DASAs have been developed (Figure 17c).…”
Section: Donor-acceptor Stenhouse Adducts (Dasas)mentioning
confidence: 99%
“…These chemotypes have attracted enormous attention owing to their facile preparation as well as their unique negative photochromic properties. [11,32,[156][157][158][159][160] DASAs are colored in the extended state and undergo Z-E isomerization and subsequent thermal conrotatory 4π electrocyclization to the compact state upon irradiation with visible light (Figure 17a,b). [161][162][163][164] Until now, three generations of DASAs have been developed (Figure 17c).…”
Section: Donor-acceptor Stenhouse Adducts (Dasas)mentioning
confidence: 99%
“…The ΔΔ G between DASA derivatives with substituents in the 3- and 4-position compared to the unsubstituted derivative show a stabilization of the closed form in line with previously published results. 29 In contrast, we found that ΔΔ G CA is increasingly positive when steric bulk is introduced to the 5-position due to steric interaction between the methyl and donor group (Fig. S15, ESI†).…”
mentioning
confidence: 88%
“…To expand our understanding of tuning the performance of DASA based systems, we targeted structural modifications on the triene backbone. Substitution on the 3-position of the backbone has been shown to favour the closed form both in donor–acceptor Stenhouse adducts as well as Stenhouse Salts, 28,29 however other substitutions have been largely overlooked. We envisioned that by finding a position on the triene backbone which increases the relative energy of the stable closed form ( i.e.…”
mentioning
confidence: 99%
“…On one hand, the effect of substitution on the properties as a whole is hard to predict and may lead to improved optical properties ( i.e ., red-shifted absorption) but poorer performance as a photoswitch. 10 On the other hand, the preparation of new DASAs with different substituents in the bridge has encountered synthetic problems. The key step for the synthesis of these compounds is usually based on the initial work by Šafář et al, 11 where the opening of furan derivatives by amines leads to the open form of DASAs through the aza-Piancatelli reaction.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Substituents in the bridge of the resulting DASA come from the substituents in positions 3 and 4 in the furan moiety. We successfully synthesized 10 different DASAs through the opening of 3-substituted furans, but all our efforts to open 3,4-disubstituted furan rings were unsuccessful. However, exploration of this substitution pattern could contribute to the better understanding of the effects of these structural changes on the performance of these switches ( Scheme 1 B).…”
Section: Introductionmentioning
confidence: 99%